The Nature of the Arab Uprising: An Analysis - Yechouti, Yahya (European Scientific Journal, ESJ, 2017)
Many scholars have pondered over the equation of the MENA region (Middle East and North Africa) and its â€œexceptionalityâ€ without being able to reach a satisfactory answer to it: what makes this region so â€œresilientâ€ to change, particularly given the rapid expansion of freedom elsewhere in the world. The Arab uprising of 2011 or what is known worldwide as the â€œArab Springâ€ was deemed to be the harbinger of the end of the â€œcurse/exceptionality,â€ the curse of this seemingly permanent state of underdevelopment, corruption, and dictatorship. But then that Arab spring itself has turned out to be rather an Arab â€œwinter,â€ further vindicating the above prejudice, and pushing a lot of yesterdayâ€™s enthusiastic crowds to be disappointed and to curse the day they thought about overthrowing their â€œbelovedâ€ dictators. Drawing on other experiences elsewhere (mainly the spring of the European peoples in 1848 and the Fall of the Berlin Wall in 1989), this essay attempts humbly to participate in this debate and to offer, on the one hand, certain relativity both to the enthusiasm and disappointment that have accompanied respectively the Arab uprising. On the other hand, and besides reviewing the prolific literature that has been written about the possible causes of the upheaval, offers â€œtentativeâ€ notes that aim to participate in the general debate with no pretention of offering a comprehensive analysis to a movement whose ins and outs are still â€œblowing in the windâ€.